2011
DOI: 10.3892/mmr.2011.666
|View full text |Cite
|
Sign up to set email alerts
|

Geranylgeranylacetone protects against myocardial ischemia and reperfusion injury by inhibiting high-mobility group box 1 protein in rats

Abstract: Abstract. The high mobility group box 1 (HMGB1) protein plays an important role in myocardial ischemia and reperfusion (I/R) injury. Geranylgeranylacetone (GGA), a heat shock protein 72 inducer, has been reported to reduce myocardial I/R injury. The aim of this study was to investigate the cardioprotective mechanism of GGA during myocardial I/R injury in rats. Anesthetized male rats were treated once with GGA (200 mg/ kg, p.o.) 24 h before ischemia, and subjected to ischemia for 30 min, followed by reperfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The mechanism were also previously explored, including by inhibiting high mobility group box 1 expression (Wang et al, 2012), increasing HSP70, caveolae formation and caveolin-3 (Tsutsumi et al, 2014), activating PI3 kinase and/or Rho kinase pathways (Zhu et al, 2005), opening the mitoK(ATP) channel (Shinohara et al, 2007), activation of PKC (Yamanaka et al, 2003), induction of thioredoxin and the activation of transcription factors such as NFkappaB and AP-1 (Hirota et al, 2000).In this study, GGA showed its ability to inhibit the neurological impairment, brain edema, inflammation, oxidative injury and neuron damage induced by cerebral I/R. To explore the molecular mechanism of GGA action, unlike the previous studies, we focused on hsp90, another HSP induced by GGA, and eNOS, an important cerebrovascular Hsp90, an adenosine triphosphate-dependent chaperone, is the major soluble protein of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism were also previously explored, including by inhibiting high mobility group box 1 expression (Wang et al, 2012), increasing HSP70, caveolae formation and caveolin-3 (Tsutsumi et al, 2014), activating PI3 kinase and/or Rho kinase pathways (Zhu et al, 2005), opening the mitoK(ATP) channel (Shinohara et al, 2007), activation of PKC (Yamanaka et al, 2003), induction of thioredoxin and the activation of transcription factors such as NFkappaB and AP-1 (Hirota et al, 2000).In this study, GGA showed its ability to inhibit the neurological impairment, brain edema, inflammation, oxidative injury and neuron damage induced by cerebral I/R. To explore the molecular mechanism of GGA action, unlike the previous studies, we focused on hsp90, another HSP induced by GGA, and eNOS, an important cerebrovascular Hsp90, an adenosine triphosphate-dependent chaperone, is the major soluble protein of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic reperfusion (IR) triggers the disturbance of microcirculation, a primary cause of cardiac failure and mortality following cardiac surgeries (1,2). Microcirculatory disturbances include endothelial cell injury, production of oxygen free radicals, energy supply reduction and myocardiocyte apoptosis (3).…”
Section: Introductionmentioning
confidence: 99%
“…Myocardial ischemia reperfusion injury is a highly complex process, and currently there are several key pathogenic mechanisms that are considered to be involved, including oxidative stress injury, intracellular calcium overload, cell apoptosis, cellular energy loss and activation of neutrophil inflammatory reaction (4). Ischemia reperfusion injury also involves multiple regulatory mechanisms, including the activation and inactivation of signaling pathways (5).…”
Section: Introductionmentioning
confidence: 99%